(untitled) (Ecological Bulletin of Kryvyi Rih District, 2025)
This article presents the results of the development of in vitro propagation protocols for species represented in the collection of the Tashkent Botanical Garden. The explants of Morus rubra L. from the botanical garden collection were introduced into culture using the in vitro method, with the influence of various phytohormones tested to optimize plant regeneration. For explant introduction, WPM (Woody Plant Medium) with 30% sucrose and 0.2 mg/l BAP was selected as the most effective nutrient medium. Rhizogenesis was successfully stimulated on a nutrient medium supplemented with 0.5 mg/l IBA. Following the successful development of root systems, a gradual acclimatization process was employed to help the plants adapt to greenhouse conditions. Initially, the plants were transferred to moist vermiculite in covered containers and kept in growth chambers for 1–2 weeks under controlled environmental conditions to minimize transplant shock and promote root system strengthening. Following this, the plants were transplanted into a peat-based substrate, kept covered to maintain high humidity, and incubated in growth chambers. Over time, the covers were gradually removed to allow the plants to adjust to ambient humidity and temperature fluctuations. This gradual acclimatization process significantly improved the survival rates and ensured the successful establishment of Morus rubra L. plants under ex vitro conditions demonstrating the effectiveness of the developed in vitro propagation protocol for this species.